PENERIMAAN INOVASI PROGRAM IMUNISASI MR (MEASLES RUBELLA) PADA MASYARAKAT DESA KAMPAR KECAMATAN KAMPA KABUPATEN KAMPAR - Sakinah, Nurul; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Indonesia has committed to achieving the elimination of Measles-Rubella and prevent CRS (Congenital Rubella Syndrome) by 2020. Measles-Rubella immunization campaign was conducted targetting children aged 9 months to under 15 years with 95% coverage. The fact is not all parents receive this innovation of immunization program. Kampar village is one of the villages with low coverage which only 20,1%. This research aims to identify the characteristics of parents who had rejected Measles-Rubella immunization and to analyze the factors that caused parents rejecting MR immunization program. This research used quantitative descriptive. The population of this research were unimmunized children aged 9 months to under 15 years totaling 1.212 children. The sampling technique was determined by using simple random sampling totaling 92 respondents. The data were collected by observation, interview and documentation. The results showed that knowledge about MR immunization is classified as “Bad” (64,1%) and did not have bad expreriences with previous immunization (67,4%). There are three dominant factors that cause parents reject MR immunization from nine factors, compatibility which is the incompatibility of MR immunization with religious rule (100%), triability which is MR immunization cannot be tried (100%) and observability which is the benefits of MR immunization cannot be observed or seen (100%).  Keywords: Innovation, Immunization, Measles and Rubella